EP.WE.555Impact of COVID 19 on Renal access surgery. (28th October 2021) - Abdelwahed, Abdallah; Gambhir, Raghvinder; Mistry, Hiren; de'figededu, Fatima; Valenti, Domenico; Rankin, Alex
Abstract: Aims: To assess the impact of COVID -19 on renal access surgery. Methods: Electronic patient records and renal ware were accessed to obtain data of all renal access activity during the COVID period. Results: There as a shutdown of all elective activity which affected the renal access surgery as well. No new Arterio venous fistulas (AVFs) were created in the time period 14 March to 05 th May 2020. No pre-fistula mapping scans were performed. All new starters started with a tunneled dialysis line. In the recovery phase special theatre sessions were asked for and procedures carried out in Day surgery and in independent sector (n-18). A total of 203 new AVF's were created compared to 272 the year before a fall of 25%. There were 48 patients admitted with blocked access, 70% of whom underwent radiological intervention compared to 52% in 2019. Surgical intervention was offered to just 4% compared to 25% in 2019. The number of access abandoned was 27% in 2020 vs 19% in 2019. Conclusion: COVID-19 adversely affected the renal access population and none of the British Renal access surgery targets were met for 2020.